MALE GENITOURINARY TRACT INFECTIONS RELATIONSHIP WITH INFERTILITY: A BACTERIOLOGICAL STUDY. - DR. RAHUL G. WADILE (International Journal of Pharma and Bio Sciences, 2013)
Asymptomatic bacteriospermia, seminal tract infections can be associated with decrease sperm count and reduces fertility, hence one of the most important causes of male infertility worldwide. Semen and Mid stream urine samples were collected under aseptic precautions, inoculated on agar mediums & incubated aerobically at 37º C for 24 hrs. Biochemical reactions were done for identification of isolated organism. Antibiotic sensitivity tests were done by modified Kirby Bauer disc diffusion method. The organisms were isolated from 83 (78.30%) seminal fluids and 75.90% urine of infertile patients. The most common organism isolated was E. coli, 17.58% & 25.40%. in cultures of semen & urine respectively. Ciprofloxacin, Ceftriaxone are the first choice of treatment. Genitourinary infections one of the causes of infertility. Despite of extended diagnosis efforts for detection of most infectious diseases, the causal relationship between infection and male infertility has not established.